Studi Farmakognostik Tanaman Inai (Lawsonia inermis Linn) asal Maluku - Jayanti Djarami; Risman Tunny (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2023)
Plants are a source of chemical compounds, both chemical compounds resulting from primary metabolism or called primary metabolites such as carbohydrates, proteins and fats which are used by the plant itself for its growth, as well as a source of secondary metabolites such as alkaloids, flavanoids, steroids/terpenoids, saponins and tannins. The design of this study was a experimental laboratory, in which morphological, anatomical, organoleptic examinations were carried out, and identification of the presence of chemical compounds in the Henna plant (Lawsonia inermis Linn) from Maluku. Morphological collation showed that the henna plant (Lawsonia inermis Linn) has single leaves facing each other. The stem is woody and thorny stems, has a taproot system. On anatomical examination, there are stomata in cross-sections and longitudinal leaves and also have vascular bundles (both xylem and phloem) in plants. In the organoleptic test, the leaves have a bitter taste and a distinctive odor at leave, while the stems and roots are tasteless and odorless. Test results Identification of the chemical content of the henna plant extract (Lawsornia inermis Linn) contains phenols, flavonoids, tannins (catechols and pyrogalotanins), saponins, steroids, and glycosides. Be observed from the chemical content of the henna plant, it can be concluded that the henna plant has medicinal properties, one of which is that it can heal cuts which the community can use for traditional medicine. It is recommended that further research be carried out to carry out pharmacological tests of henna plants on experimental animals. Keywords: Pharmacognostic Study, Henna, Chemical Content, Traditional Medicine